Ulam–Hyers–Rassias stability of neutral stochastic functional differential equations. Issue 6 (18th August 2022) - Caraballo, Tomás; Mchiri, Lassaad; Rhaima, Mohamed
Abstract : In this paper, by using the Gronwall inequality, we show two new results on the Ulam–Hyers and the Ulam–Hyers–Rassias stabilities of neutral stochastic functional differential equations. Two examples illustrating our results are exhibited.